PENERAPAN METODE VARIASI DAN LATIHAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA MATERI MEMBANDINGKAN PECAHAN PADA SISWA KELAS III SDN CIKUBANGSARI TAHUN AJARAN 2022/2023 - Suratmi, Titin (Jurnal Sains Indonesia, 2022)
This study aims to improve learning outcomes on the material of sorting fractions through the method of variation and practice for third grade students of SDN Cikubangsari in the academic year of 2022/2023. The subjects who were subjected to the action were the third grade students of SDN Cikubangsari, Kramatmulya District, Kuningan Regency with a total of 15 people, consisting of 8 male students and 7 female students. Each action includes the stages of planning, implementing actions, observing and reflecting. The instruments used in this study were observation and tests. The observation sheet is used to determine the attitudes, interactions and participation of students and teachers in the learning process, while the test results are used to determine the level of student mastery in solving questions and the diversity of students' answers to the questions given. This study aims to improve student learning outcomes and interest by using variation and practice methods. This can be seen by the creation of an active and conducive atmosphere during learning and an increase in the average score and the percentage of student learning achievement that increases in each cycle.